Online Resources to Support Clinical Practice. (March 2018) - Ko, Arthur; Turner, Jill
Abstract : Evidence-based practice requires access to practice guidelines, research articles, and other resources; however, home healthcare clinicians can face barriers when seeking health information. The purpose of this article is to provide home care clinicians with: a) free resources available on the internet, b) suggestions for searching and evaluating health information found on the internet, and c) opportunities for free continuing education for home healthcare clinicians.